Analysis Of the Effect Of Impermeability Test On Laminated Board Systems Bamboo Petung On Ship Shell Material Joints - Parlindungan Manik; Sarjito Jokosisworo; Tuhfan Jawahiru Basyari (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Wood material is one of the materials in the manufacture of shipAnother alternative is bamboo. Bamboo material plays an important role because bamboo has another advantage of this bamboo, which is lightweight and has a fairly high flexibility. To make a good bamboo board, a strong adhesive and combination of components is needed for shipbuilding. In this study, the type of bamboo used was petung bamboo. The purpose of this study was to determine how the effect of the tightness test on the petung bamboo laminated board system at the ship’s shell material connection and to determine the value of the tightness used to test the petung bamboo laminated board system on the ship's material connection. Meanwhile, the benefit of the research is to provide understanding and insight on various matters relating to the Impermeability Test of the Petung Bamboo Laminated Board System at the Connection of the Vessel Material. The method in this study uses the standard Air Pressure Test which aims to see whether or not it can be applied to bamboo ship building technology. This test uses a pressure ranging from 0.2 psi. The results of this study showed that the vertical joint laminated board showed 140.2 lbf/in2 and 139.4 lbf/in2 while the inclined joint laminate board is 124.4 lbf/in2and 123.8 lbf/in2.